To solve this expression, we can use the division rule of fractions.
To divide fractions, we flip the second fraction and multiply it by the first fraction.
1/6 ÷ 1/3 = 1/6 × 3/1
To multiply fractions, we multiply the numerators together and the denominators together.
1/6 × 3/1 = (1 × 3) / (6 × 1) = 3/6
We can simplify this fraction by dividing both the numerator and denominator by their greatest common divisor, which is 3.
3/6 ÷ 3/6 = (3 ÷ 3) / (6 ÷ 3) = 1/2
Therefore, 1/6 ÷ 1/3 simplifies to 1/2.
Compute: 1/6÷1/3 . Simplify the answer if possible.
1 answer